Implikasi Wanita Karir Terhadap Keharmonisan Rumah Tangga Perspektif Hukum Islam - Abqori, Najih; Rizqi, Elisa Mukaromah (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2024)
The increasing number of career women in modern society introduces new dynamics to domestic life, particularly in balancing household and professional roles. In Krumpakan Village, Kajoran, Magelang, women juggling responsibilities as wives, mothers, and professionals face diverse implications for household harmony. From an Islamic legal perspective, maintaining a balance between family duties and career is crucial for upholding family unity in line with sharia principles. This study explores the impact of career women on household harmony in Krumpakan Village, examining both positive and negative aspects while analyzing their alignment with Islamic law. Using a qualitative descriptive approach, data were gathered through in-depth interviews with career women, their husbands, and religious figures, as well as direct observation of their domestic life. Findings reveal that career women contribute positively to household harmony, such as enhancing family income, but also face challenges like reduced family time and the strain of dual roles. Islamic law permits women to work as long as they fulfill their duties as wives and mothers and adhere to sharia principles. Supportive partners and equitable task distribution are critical to achieving a balance between career and home life. This study concludes that household harmony can be sustained through the synergy of career women's roles, family support, and adherence to Islamic legal values.